Adipokinetic Hormone Receptor Mediates Lipid Mobilization to Regulate Starvation Resistance in the Brown Planthopper, Nilaparvata lugens - Lu, Kai; Zhang, Xinyu; Chen, Xia; Li, Yue; Li, Wenru; Cheng, Yibei; Zhou, Jinming; You, Keke; Zhou, Qiang (Frontiers in Physiology, 2018)
Lipid storage must be efficiently mobilized to sustain the energy demands during processes of exercise or starvation. In insects, adipokinetic hormone (AKH) and brummer lipase are well-known regulators of lipid mobilization. We recently demonstrated that brummer-dependent lipolysis regulates starvation resistance in the brown planthopper, Nilaparvata lugens, one of the most destructive rice pests. The present work investigated the roles of the AKH signaling system in lipid mobilization during the starvation process in N. lugens. NlAKHR is a typical G protein-coupled receptor (GPCR) and possesses high structure and sequence similarity to other insect AKHRs. Spatial and developmental expression profiles suggested that NlAKH is released from the corpora cardiaca to activate NlAKHR mainly expressed in the fat body. Starvation significantly induced the expression of NlAKH and NlAKHR, indicating a potential role of the AKH signaling system in starvation resistance. To reveal the functions of the AKH signaling system, a double-stranded RNA (dsRNA)-mediated knockdown of NlAKHR and NlAKH peptide injection was performed. The results show NlAKHR silencing decreased the levels of 1,2-diacylglycerol (DAG) in the hemolymph and increased triacylglycerol (TAG) levels in the fat body, whereas NlAKH injection led to a critical accumulation of DAG in the hemolymph and a severe reduction of TAG content in the fat body. Knockdown of NlAKHR resulted in prolonged lifespan and high levels of whole-body TAG, indicating an inability to mobilize TAG reserves during starvation. Conversely, the NlAKH injection reduced the survival and accelerated TAG mobilization during starvation, which further confirms the role of NlAKH in lipolysis. Moreover, NlAKHR silencing caused obesity in N. lugens, whereas NlAKH injection depleted organismal TAG reserves in vivo and produced a slim phenotype. These results indicate that lipid mobilization is regulated by the AKH signaling system, which is essential for adjusting body lipid homeostasis and ensuring energy supplement during starvation in N. lugens.